2017
DOI: 10.3390/ijms18061175
|View full text |Cite
|
Sign up to set email alerts
|

The Combination of Arginine Deprivation and 5-Fluorouracil Improves Therapeutic Efficacy in Argininosuccinate Synthetase Negative Hepatocellular Carcinoma

Abstract: Argininosuccinate synthetase (ASS), a key enzyme to synthesize arginine is down regulated in many tumors including hepatocellular carcinoma (HCC). Similar to previous reports, we have found the decrease in ASS expression in poorly differentiated HCC. These ASS(-) tumors are auxotrophic for arginine. Pegylated arginine deiminase (ADI-PEG20), which degrades arginine, has shown activity in these tumors, but the antitumor effect is not robust and hence combination treatment is needed. Herein, we have elucidated th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 43 publications
0
16
0
Order By: Relevance
“…Its anti-angiogenic activity suggests that ADI could become a novel anti-cancer drug targeting neovascularization-related tumors. In other studies, ADI-PEG20 treatment downregulated thymidylate synthase and interfered with pyrimidine synthesis [65,78]. This is of particular relevance for combination approaches using the standard chemotherapeutic drug 5-Fluorouracil (5-FU).…”
Section: Strategies To Improve Adi-based Therapymentioning
confidence: 99%
“…Its anti-angiogenic activity suggests that ADI could become a novel anti-cancer drug targeting neovascularization-related tumors. In other studies, ADI-PEG20 treatment downregulated thymidylate synthase and interfered with pyrimidine synthesis [65,78]. This is of particular relevance for combination approaches using the standard chemotherapeutic drug 5-Fluorouracil (5-FU).…”
Section: Strategies To Improve Adi-based Therapymentioning
confidence: 99%
“…We and others proposed that anticancer therapy based on single-amino-acid arginine deprivation that utilizes recombinant arginine-degrading enzymes could be applied as an antiglioblastoma treatment [ 1 , 24 , 25 ]. This metabolic approach has already achieved significant progress in cell culture and animal studies, and in clinical trials aimed at a growing number of cancer types [ 68 ]. Although the feasibility of this approach for the treatment of various cancers, primarily those with defects in arginine anabolism, has been demonstrated [ 67 , 68 ], we have found that the strong antitumor effect of arginine starvation observed in standard in vitro monolayer cell cultures does not fully translate into 3D cultures [ 69 ].…”
Section: Discussionmentioning
confidence: 99%
“…This metabolic approach has already achieved significant progress in cell culture and animal studies, and in clinical trials aimed at a growing number of cancer types [ 68 ]. Although the feasibility of this approach for the treatment of various cancers, primarily those with defects in arginine anabolism, has been demonstrated [ 67 , 68 ], we have found that the strong antitumor effect of arginine starvation observed in standard in vitro monolayer cell cultures does not fully translate into 3D cultures [ 69 ]. We and others proposed, therefore, that rationally designed combinational modalities are needed for the approach to successfully proceed into clinical use [ 1 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar to this finding, it has been shown that in human pancreatic cancer ( 26 ), HCC, myxofibrosarcoma and bladder cancer, decreased ASS expression correlated with histopathological grading ( 27 ). For instance, a 1.29-fold reduction of ASS expression in tumor cells of HCC specimens was associated with poor tumor differentiation ( 21 ). However, there was no association found between ASS expression and histopathological characteristics of tumors in a cohort study of lung cancer patients ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…ASS expression in CCA specimens was classified as low or high according to a previous report ( 21 ). Briefly, IHC analysis of ASS and Ki-67 expression in CCA specimens was determined by HistoFAXS software Version 4.1 and viewed at 100× magnification.…”
Section: Methodsmentioning
confidence: 99%